Effects on Mechanical Properties of Recycled PET in Cement-Based Composites - Liliana Ávila Córdoba; Gonzalo Martínez-Barrera; Carlos Barrera Díaz; Fernando Ureña Nuñez; Alejandro Loza Yañez (International Journal of Polymer Science)
Concretes consisting of portland cement (OPC), silica sand, gravel, water, and recycled PET particles were developed. Specimens without PET particles were prepared for comparison. Curing times, PET particle sizes, and aggregate concentrations were varied. The compressive strength, compressive strain at yield point, and Young modulus were determined. Morphological and chemical compositions of recycled PET particles were seen in a scanning electron microscopy. Results show that smaller PET particle sizes in lower concentrations generate improvements on compressive strength and strain, and Young’s modulus decreases when the size of PET particles used was increased.